To find the average of an amount of numbers, we simply add them up and divide them by the amount of numbers we have. For example, if we have 1,2, and 3 as our numbers, we can see that we have three numbers. Next, we add them up to get 1+2+3=6. Lastly, we divide 6 by the amount of numbers we have (3) to get 6/3=2 as our average. Applying that here, we see that there are four numbers. Next, we add them up using a calculator to get 5,678.54+3,665.77+4,231.98+4,768.99 =18345.28 . Finally, we divide that number by the amount of numbers we have (using a calculator) to get 18345.28/4=4,586.32, making B your answer.
Feel free to ask further questions, and Happy Halloween!
Answer:
Part a) The scale of the new blueprint is
Part b) The width of the living room in the new blueprint is
Step-by-step explanation:
we know that
The scale of the original blueprint is
and
the width of the living room on the original blueprint is 6 inches
so
Find the actual width of the living room, using proportion
Find the actual length of the living room, using proportion
Find the scale of the new blueprint, divide the length of the living room on the new blueprint by the actual length of the living room
simplify
Find the width of the living room in the new blueprint, using proportion
Answer:
Step-by-step explanation:
Step 1: Sum of angles on a straight line is 180
Step 2:
2x + 25 + y = 180
2x + y = 180 - 25
2x + y = 155 (1)
Step 3:
3x - 10 + y = 180
3x + y = 180 + 10
3x + y = 190 (2)
Step 4: Substract equation 1 from 2
3x + y - 2x - y = 190 - 155
x = 35
Step 5:
Substitute x in equation 1 to find y
2x + y = 55
2(35) + y = 155
70 + y = 155
y = 155 - 70
y = 85
Answer:
Each hot dog = $3
Each french fry = $2
Step-by-step explanation:
First, lets define our variables:
x = Hotdog
y = fries
Next, you need to set up a cost equation for both Toby and Bernie:
8x + 5y = 34
2x + 6y = 18
Now, we need to isolate one of the variable:
2x + 6y = 18
2x = 18 - 6y
x = 9 - 3y
Next, we need to insert this equation back into the first equation (8x+5y = 34) to find the cost of y (fries):
8x +5y = 34
8 (9-3y) + 5y = 34
72 - 24y + 5y = 34
72 - 19y = 34
19y = 38
y or fries = $2
Finally, we need to find the cost of each hotdog by using the cost of fries ($2) in one of the formulas:
2x + 6y = 18
2x + 6(2) = 18
2x + 12 = 18
2x = 6
x or hotdog = $3
I hope this helps!
-TheBusinessMan